Experimental and numerical study of coal-rock bimaterial composite bodies under triaxial compression - Chen, Yulong; Zuo, Jianping; Liu, Dejun; Li, Yingjie; Wang, Zhenbo (International journal of coal science & technology, 2021)
To accurately predict coal burst hazards and estimate the failure of coal pillars in underground coal mining systems, it is of great significance to understand the mechanical behavior of coal-rock bimaterial composite structures. This paper presents experimental and numerical investigations on the response of rock-coal, coal-rock, and rock-coal-rock bimaterial composite structures under triaxial compression. The triaxial compression experiments are conducted under confining pressures in the range of 0–20 MPa. The resulting inside fracture networks are detected using X-ray-based computed tomography (CT). The experimentally observed data indicate that the mechanical parameters of the rock-coal-rock composites are superior to those of the rock-coal and coal-rock combinations. After compression failure, the coal-rock combination specimens are analyzed via X-ray CT. The results display that the failure of the coal-rock composite bodies primarily takes place within the coal. Further, the bursting proneness is reduced by increasing confining pressure. Subsequently, the corresponding numerical simulations of the experiments are carried out by using the particle flow code. The numerical results reveal that coal is vulnerable with regard to energy storage and accumulation.